2007
DOI: 10.1007/s10661-007-9800-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecological quality boundary-setting procedures: the Gulf of Riga case study

Abstract: Two approaches for setting ecological class boundaries, response curves and a simplified mathematical boundary-setting protocol, were tested for coastal, transitional and open waters in the Gulf of Riga, Baltic Sea. The simplified mathematical boundary-setting protocol defines acceptable ecological status based on expert judgment by a uniform relative deviation from reference conditions. In contrast, response curves derive class boundary definitions from observed changes in biological quality elements along en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Very few studies define threshold concentrations supporting good ecological status in coastal waters. Of those that have been performed, Aigars et al (2008) found that marked changes in biological communities occur at winter SRP concentrations >23 μg-P L −1 or 28 μg-P L −1 (southern and central part of the Gulf of Riga); these values correspond to the good-moderate threshold for regional type BC4 (23 μg L −1 ). Salas Herrero et al (2019) derived good-moderate thresholds of 18 μg TP L −1 for MED Type IA and 13 μg TP L −1 for MED Type II A, which are similar to the TP criteria set by countries sharing these types (Table 6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Very few studies define threshold concentrations supporting good ecological status in coastal waters. Of those that have been performed, Aigars et al (2008) found that marked changes in biological communities occur at winter SRP concentrations >23 μg-P L −1 or 28 μg-P L −1 (southern and central part of the Gulf of Riga); these values correspond to the good-moderate threshold for regional type BC4 (23 μg L −1 ). Salas Herrero et al (2019) derived good-moderate thresholds of 18 μg TP L −1 for MED Type IA and 13 μg TP L −1 for MED Type II A, which are similar to the TP criteria set by countries sharing these types (Table 6).…”
Section: Discussionmentioning
confidence: 94%
“…While threshold concentrations in coastal waters should also be based on knowledge of measurable biological response (Devlin et al, 2007) progress has been limited (but see Aigars et al, 2008; Salas Herrero et al, 2019). A common approach in the North Sea and Baltic Sea is to model historic nutrient inputs using catchment models and extrapolating these to coastal waters using a modelling approach or mixing diagrams (Schernewski et al, 2015; Ibisch et al, 2016; Blauw et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All of the analysed exponential relationships (Figs 3 and 4), with the exception of chlorophyll-a vs. Secchi depth, were ascent curves and did not show clear break points that could be defined as borders between specific ecological quality states (Aigars et al 2007). This observation is easily explained as the area of the Gulf of Gdańsk has been under heavy anthropogenic influence for a much longer time than the analysed data series.…”
Section: Response Curvesmentioning
confidence: 93%
“…Central Polish coast, st. L7 The spreading of data around the regression curves suggests the possibility of strong exponential relationships that could be used for class boundary definitions (Aigars et al 2007), and so exponential relationships were also analysed (Table 4); these exponential correlations are shown in Figures 3 and 4. All of the analysed exponential relationships (Figs 3 and 4), with the exception of chlorophyll-a vs. Secchi depth, were ascent curves and did not show clear break points that could be defined as borders between specific ecological quality states (Aigars et al 2007).…”
Section: Response Curvesmentioning
confidence: 99%
“…Since only a few worldwide monitoring programs date from prior to the 1970s, there is a general lack of historical measurement data with regard to biological quality elements. Therefore, the reference values and class boundaries were to be derived from functional relations (Aigars et al 2008, Devlin et al 2007, Andersen et al 2010. The marine environment of the southern Baltic Sea, including the Polish sector, has been heavily impacted by human activity for a long time (Głowińska 1963, Trzosińska 1978, Łysiak-Pastuszak 2000, HELCOM 2009), and it is therefore not possible to obtain reference conditions from the data collected within the marine monitoring programs, which were generally initiated during the 1970s or later (HELCOM 2006).…”
Section: Introductionmentioning
confidence: 99%